Implementasi Strategi Pembiasaan dan Keteladanan dalam Meningkatkan Literasi Keagamaan Siswa di SMP Negeri 1 Lembah Sabil, Aceh Barat Daya - Afdhalurrahman; Wahyuddin Nur Nst; Mohammad Al-Farabi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Students’ religious literacy has become an important concern in Islamic Religious Education, especially in the digital era when students encounter various religious information without always being supported by adequate understanding and consistent religious practice. This study aims to analyze students’ religious literacy, identify the factors contributing to its decline, and examine the implementation of habituation and role modeling strategies at SMP Negeri 1 Lembah Sabil, Southwest Aceh. This research used a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation involving the principal, Islamic Religious Education teachers, and students as informants. The data were analyzed through data condensation, data display, and conclusion drawing, while data validity was maintained through source triangulation and technique triangulation. The findings show that students’ religious literacy is in a fairly good condition but not yet optimal. Students have understood the basic teachings of Islam, participated in religious activities, and demonstrated positive religious behavior; however, some students still lack intrinsic awareness and consistency in practicing religious values independently. This condition is influenced by low motivation, weak self-awareness, family environment, peer influence, uncontrolled use of digital media, and limited parental supervision. The habituation strategy is implemented through prayer, Qur’an recitation, congregational prayer, short religious talks, and Islamic etiquette, while the role modeling strategy is reflected in teachers’ discipline, politeness, and consistent moral behavior. These two strategies complement each other effectively.